Sistem Pemantauan Tanaman Dalam Pot Indoor Dengan Internet of Things - Muhammad Iqbal Setiawan; Bachtiar Efendi; Abdul Karim Syahputra (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study discusses the design and implementation of an Internet of Things (IoT)-based indoor potted plant monitoring system, which aims to help users care for plants in a more effective and efficient manner. The system uses an ESP32 microcontroller connected to a DHT22 sensor to measure air temperature and humidity, soil moisture, an LDR to measure light intensity, and a TDS sensor to monitor nutrient levels in the water. Data collected from the sensors is transmitted directly via a WiFi connection to an MQTT broker, displayed on a Node-RED dashboard, and stored in Firebase for historical documentation purposes. This system has two operational modes, manual and automatic, allowing users to control the water pump and grow light directly or let the system operate based on pre-set parameters. Test results show that all sensors function accurately and respond to changes in environmental conditions, thereby improving efficiency in watering and lighting. The advantage of this system lies in the integration of four monitoring parameters into a single platform that is easy to use, flexible, and widely accessible. This research is expected to provide practical solutions for urban agriculture and the development of smart farming at the household level, although further testing on various plant types and environmental conditions is still needed for further refinement